HUKUM TERHADAP SANKSI PIDANA BAGI PEMBERI KERJA DALAM PENYELENGGARAAN PROGRAM JAMINAN KESEHATAN NASIONAL (JKN) - Rahman, Zikril; Tumuhulawa, Arifin; Amu, Robby W. (At-Tanwir Law Review, 2025)
This study analyzes criminal law policies for employers in the National Health Insurance (NHI) Program under Law No. 24 of 2011. Articles 54 and 55 regulate criminal sanctions but do not clearly classify violations as crimes or offenses, nor sufficiently incorporate the element of unlawfulness. Article 55 also adopts an alternative sentencing system, allowing imprisonment to be replaced with fines. Sanctions target employers who fail to register employees or remit contributions. The study concludes that law enforcement requires improved regulatory formulation, oversight, and synergy between BPJS, law enforcement agencies, and society.